2019
DOI: 10.1073/pnas.1817849116
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers and infants expect individuals to refrain from helping an ingroup victim’s aggressor

Abstract: Adults and older children are more likely to punish a wrongdoer for a moral transgression when the victim belongs to their group. Building on these results, in violation-of-expectation experiments (n= 198), we examined whether 2.5-year-old toddlers (Exps. 1 and 2) and 1-year-old infants (Exps. 3 and 4) would selectively expect an individual in a minimal group to engage in third-party punishment (TPP) for harm to an ingroup victim. We focused on an indirect form of TPP, the withholding of help. To start, childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 85 publications
(125 reference statements)
4
43
0
1
Order By: Relevance
“…Together with the present results, these findings support the view that beginning early in life, interventions 1) are expected for leaders who observe within-group transgressions, as their position of leadership protects them somewhat from the risk of retaliation, but 2) are considered optional for nonleaders who observe within-group transgressions and for individuals who observe anonymous transgressions. Second, the results of the nonleader condition also bear on recent findings that 13-and 29-mo-olds expected a nonleader who had observed a transgression against an ingroup victim to engage in indirect third-party punishment toward the wrongdoer, by withholding help (50). Following the transgression, while the nonleader watched, the wrongdoer worked at a task and needed instrumental assistance to complete it.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Together with the present results, these findings support the view that beginning early in life, interventions 1) are expected for leaders who observe within-group transgressions, as their position of leadership protects them somewhat from the risk of retaliation, but 2) are considered optional for nonleaders who observe within-group transgressions and for individuals who observe anonymous transgressions. Second, the results of the nonleader condition also bear on recent findings that 13-and 29-mo-olds expected a nonleader who had observed a transgression against an ingroup victim to engage in indirect third-party punishment toward the wrongdoer, by withholding help (50). Following the transgression, while the nonleader watched, the wrongdoer worked at a task and needed instrumental assistance to complete it.…”
Section: Discussionsupporting
confidence: 57%
“…This suggested that infants would perceive the wrongdoer and the victim, 2 group members of equal standing, to be entitled to an equal share of the toys, and hence that they would detect a fairness transgression when the wrongdoer took both toys, leaving none for the victim. Finally, there is also evidence that infants aged 12 to 17 mo possess an abstract expectation of ingroup support: For example, individuals in a group are expected to care for each other by refraining from unprovoked harm and by providing assistance when needed (47)(48)(49)(50). This suggested that infants would also perceive an ingroup-support transgression in our events and would be particularly sensitive to the plight of the victim, who was treated unfairly by a member of her own group.…”
Section: The Present Researchmentioning
confidence: 97%
“…When shown instances of one person harming another, both 1-year-olds and 2.5-year-olds expect someone who shares group membership with the victim to harm (i.e., withhold help from) the transgressor in the future (Baillargeon et al, 2015;Ting, He, & Baillargeon, 2019).…”
Section: Evidence From Infancymentioning
confidence: 99%
“…Mesmo que, ao longo de sua história, nossa espécie tenha demonstrado sua capacidade de praticar formas de cooperação aberta , abrangendo a família, o clã, a comunidade ou a nação, a oposição "Nós vs Eles", o que eu chamo de conformação cognitiva do grupo, é sem dúvida um invariante antropológico (BERNHARD et al, 2006;CHOI;BOWLES, 2007). Em geral, os seres humanos têm uma forte propensão a favorecer seu grupo de pertencimento e julgá-lo superior aos outros -ou mais "normal" que os outros -, desde a primeira infância (JIN;BAILLARGEON, 2017;TING et al, 2019) e todos os sexos combinados, embora os homens sejam mais inclinados a isso que as mulheres (ROMANO et al, 2017). Como explicar o significado dessa conformação cognitiva?…”
Section: Por Que Uma Conformação Cognitiva Grupalunclassified